Resposta :
Oie, Td Bom?!
[tex] = ( \sqrt{3} - \sqrt{2} ) \: . \: ( \sqrt{3 \sqrt{2} } )[/tex]
[tex] = \sqrt{3} \sqrt{3 \sqrt{2} } - \sqrt{2} \sqrt{3 \sqrt{2} } [/tex]
[tex] = \sqrt{9 \sqrt{2} } - \sqrt{6 \sqrt{2} } [/tex]
[tex] = \sqrt{ 3{}^{2} \sqrt{2} } - \sqrt{ \sqrt{6 {}^{2} } \sqrt{2} } [/tex]
[tex] = \sqrt{3 {}^{2} } \sqrt{ \sqrt{2} } - \sqrt{ \sqrt{6 {}^{2} } \sqrt{2} } [/tex]
[tex] = 3 \sqrt{ \sqrt{2} } - \sqrt{ \sqrt{6 {}^{2} } \sqrt{2} } [/tex]
[tex] = 3 \sqrt[2 \: . \: 2]{2} - \sqrt{ \sqrt{6 {}^{2} \: . \: 2 } } [/tex]
[tex] = 3 \sqrt[4]{2} - \sqrt{ \sqrt{6 {}^{2} \: . \: 2 } } [/tex]
[tex] = 3 \sqrt[4]{2} - \sqrt{ \sqrt{36 \: . \: 2} } [/tex]
[tex] = 3 \sqrt[4]{2} - \sqrt{ \sqrt{72} } [/tex]
[tex] = 3 \sqrt[4]{2} - \sqrt[2 \: . \: 2]{72} [/tex]
[tex] = 3 \sqrt[4]{2} - \sqrt[4]{72} [/tex]
[tex]≈0,654...[/tex]
Att. Makaveli1996
[tex](\sqrt{3}-\sqrt{2})\cdot(\sqrt{3\sqrt{2}})\\\\\sqrt{3}\sqrt{3\sqrt{2}}-\sqrt{2}\sqrt{3\sqrt{2}}\\\\\sqrt{3\cdot3\sqrt{2}}-\sqrt{2\cdot3\sqrt{2}}\\\\\sqrt{9\sqrt{2}}-\sqrt{6\sqrt{2}}[/tex]
É o máximo que da pra fazer